Allochrony of neighbour ecological species: Can isolation by time maintain divergence? The natural experiment of sympatric Nothofagus - Juri, Gabriela; Premoli Il'grande, Andrea Cecilia (Forest Ecology and Management)
Ecological mechanisms that maintain species identity between potentially interfertile sympatric populations are puzzling. Local adaptation to a particular environment by means of phenology may confine plants to very specific habitats that may result in assortative mating within an initially panmictic population. Nothofagus pumilio, N. antarctica and N. dombeyi are sister species. They can occur in sympatry and are known to interbreed but they are morphologically and ecologically different. We recorded leafing and flowering phenologies and their thermal requirements to reach each phenophase at distinct locations during three growing seasons (2016–2018). We compared data for sympatric and allopatric populations of different species, sites and elevations. Sympatric populations of different species have contrasting thermal requirements and thus uncoupled phenologies. Temperature, through differences in elevation, is the main driver of intraspecific phenological differences at the population level. Low elevation populations flower earlier than high elevation ones. Allopatric populations of each species are synchronic and reproductively linked to some degree. A combination of high ecological specialization and strong phenological pre-pollination barriers operate together to temporally isolate distinct species, against the homogenizing effect of the occasional or even persistent gene flow. The eventual hybrid formation could be negatively selected by strong local selection to contrasting environments. Fil: Juri, Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina. Universidad Nacional de Río Negro. Sede Andina. Instituto de Investigaciones en Recursos Naturales, Agroecología y Desarrollo Rural; Argentina Fil: Premoli Il'grande, Andrea ...